(untitled) (Journal of Management & Business, 2022)
The objective of the work proposed in this article was to determine the public position of the Chilean Undersecretariat of the Environment, which has the most consigned audiences between the years 2015-2019, in addition to the frequency of reported matters. It was established that, the position of Minister, is the public authority that has the most audiences assigned during the surveyed period of the Undersecretariat of the Environment and the most recurrent matter to be dealt with was the “design, implementation and evaluation of policies, plans and programs carried out by taxpayers”. To carry out this work, an exhaustive collection of useful data was carried out, from the public records of the Undersecretariat of the Environment, and from positions of the Council for Transparency. Background, which once collected and were ordered and put to the test under a very frequent study method in social sciences, as is the case of comparative studies, through which a Rankin was established, with the positions with the most audiences consigned among the years of scrutiny.